Bubble characteristics from injected air sheet through slots in a water cross-flow. (September 2021) - Dhar, Leila; Anne, Florentin; Recchia, Grégoire; Etienne, Stéphane; Béguin, Cédric; Scott, David; Bornard, Laurent
Highlights: Air injection at high flow rate through slots into a water cross-flow is studied. Bubble characteristics along the gas pathway are investigated with an optical probe. Pressure losses through the injection and along the test section are examined. Influence of slot geometries and flow rates on bubble parameters are analyzed. Self-similarities of void fraction in the altitude direction are highlighted. Abstract: While air injection has already been widely studied for stagnant water at low air injection rates for circular injectors, limited data is available on gas in liquid cross-flows injected through slots at high air flow rates. The key purpose of this work is to observe the evolution of bubble swarm characteristics for simple geometries such that, by correlation rules, these characteristics can be projected for more complicated geometries and environment. To that effect, an experimental water loop with both controllable water and air flow rates is used to generate bubble clouds with cross-flow air injection. Measurements with an optical probe allow the void fraction, the size and velocity of bubbles to be measured. The findings show that the general size of bubbles increases with an increase in the air flow rate for a constant water flow rate. Furthermore, bubbles pick up speed while moving away from the injection slot. Bigger bubbles travel faster than small ones ; they also tend to rise to the top of bubble plumes while small bubbles stay in the lower portion. Finally, the maps of void fraction indicate that its local values drop while heading away from the injection slot.